2015
DOI: 10.1001/jamaoto.2015.0786
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Observation vs Prophylactic Selective Level VI Neck Dissection for Papillary Thyroid Carcinoma at a Cancer Center

Abstract: Although the risk for occult lymph node metastasis reached 67.2% in a selected group of patients, elective central neck dissection for patients with PTC increased the risk for complications and did not contribute to a decrease in local recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 73 publications
5
48
0
1
Order By: Relevance
“…Therefore, the 2015 American Thyroid Association (ATA) Management Guidelines recommend CND for T3 or T4 PTC, as it improves disease‐specific survival and reduces local recurrence . On the other hand, routine performance of CND in low‐risk PTC patients is not recommended because several studies show that CND is associated with higher rates of complications . However, the actual incidence of permanent hypocalcaemia after thyroidectomy is difficult to estimate due to its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the 2015 American Thyroid Association (ATA) Management Guidelines recommend CND for T3 or T4 PTC, as it improves disease‐specific survival and reduces local recurrence . On the other hand, routine performance of CND in low‐risk PTC patients is not recommended because several studies show that CND is associated with higher rates of complications . However, the actual incidence of permanent hypocalcaemia after thyroidectomy is difficult to estimate due to its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of normal parathyroid glands is essential for their preservation during thyroidectomy in thyroid diseases to avoid the major complications of hypoparathyroidism . It is also critical in patients with minimally invasive parathyroid surgery and focused parathyroidectomy to replace the traditional 4‐gland parathyroid exploration.…”
mentioning
confidence: 99%
“…CLND has several associated risks, including increased risk of hypoparathyroidism and recurrent laryngeal nerve injury over thyroidectomy alone (28). A meta-analysis of over 3,000 patients found that temporary hypocalcemia and temporary vocal cord paralysis were more common in patients undergoing CLND versus thyroidectomy alone but that there were no differences in permanent hypocalcemia or vocal cord injury (23).…”
Section: Benefits and Risks Of Prophylactic Central Neck Lymph Node Dmentioning
confidence: 99%